QUANTITATIVE STRUCTURE – ACTIVITY RELATIONSHIP OF SUBSTITUTED GLUCOSYLFLAVONE AND ITS ANALOGUES BY MOLECULAR ORBITAL AND LINEAR FREE ENERGY APPROACHES - Louis, C.; Robert, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Glucosylflavone (5-hydroxy7-methoxy6c-glucosylflavone) the active principle from a natural source (Sphaeranthus indicus Linn) has been extracted and its medicinal activity assessed. An attempt has been made in this study to evaluate the structure – activity relationship of the active principle of this important medicinal plant and its structural analogues based on Molecular Orbital and Linear free energy approaches. The structure plays an important role both in the cases of structurally specific and non-specific drugs. As the characteristics of structurally non-specific drugs depend on the equilibrium conditions, the concentration of the drugs in cell lipids becomes an important criterion in deciding about the efficacy of the drugs. The partition coefficient of the active principle and its analogues indicate that the methoxy, ethoxy and propoxy substituents increase thereby hinting at a lower requirement of the propoxy substituted derivative at a lower concentration. Higher -oxy- derivatives did not bring about the proportionate advantage. The molar refractivities and the Connolly Accessible area of the active principle and the analogues highlight the structure- activity correlation of the models studied and their synthesis and pharmacological evaluation. As the binding of the drugs to protein enforce steric constraints, structural tailoring needs to consider the steric energy of molecular models. The steric energy of the analogues are computed using GAUSSIAN03 at B3LYP 6-31G wave function and compared with that of the active principle. The molar refractivities of the active principle and the molecular models range between 111.4 to 120 cm3/mol highlighting the distinct correlation between the structure and the biological activity.